1987
DOI: 10.1159/000234336
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Monoclonal IgM Rheumatoid Factor to Streptococci via the Antibody Combining Site

Abstract: Radiolabelled monoclonal IgM rheumatoid factors, four from patients with type II essential cryoglobulinaemia and one originating from a patient with rheumatoid arthritis, were tested for binding to group A, B, C and G streptococci and Escherichia coli Two of the preparations exhibited different binding patterns for the streptococci, whereas the remaining three were not reactive. The binding of one of the factors to group A streptococci type 15 was inhibited by F(ab′)2-fragments of anti-idiotypic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Compared to the RF seronegative periodontitis patients, the RF seropositive patients show significantly elevated serum IgG and IgM antibody levels to oral microorganisms (The & Ebersole 1996). Increases in IgM-RF noted in periodontitis could result from chronic antigenic stimulation by the bacterial plaque or by specific members of the microbiota with cross-reactive epitopes as has been suggested with streptococcal antigen (Schroder et al 1987, Moore et al 1989). The definite role of periodontitis-induced RF on the severity and progression of RA is still unknown.…”
Section: Rheumatoid Factorsmentioning
confidence: 97%
“…Compared to the RF seronegative periodontitis patients, the RF seropositive patients show significantly elevated serum IgG and IgM antibody levels to oral microorganisms (The & Ebersole 1996). Increases in IgM-RF noted in periodontitis could result from chronic antigenic stimulation by the bacterial plaque or by specific members of the microbiota with cross-reactive epitopes as has been suggested with streptococcal antigen (Schroder et al 1987, Moore et al 1989). The definite role of periodontitis-induced RF on the severity and progression of RA is still unknown.…”
Section: Rheumatoid Factorsmentioning
confidence: 97%
“…A number of studies have reported generation of RF-like antibodies in animals immunized with bacterial and viral Ig-binding proteins [1][2][3][4][5][6][7][8][9][10][11]. Three possible explanations have been proposed to account for generation of these antibodies and for the finding that the resulting species reactivity profile of the anti-IgGbinding antibody mimics the reactivity profile of the bacterial or viral Fc-binding protein immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial immunoglobulin (Ig)G-binding proteins, such as staphylococcal protein A and streptococcal protein G, have many similarities in their reactivity to a family of autoantibodies against IgG, designated rheumatoid factors (RF), and present in the serum of certain patients with rheumatoid arthritis [1][2][3][4][5][6][7][8][9]. Rheumatoid factors and bacterial IgG-binding proteins bind to a similar site on the Fc region of IgG and also demonstrate similar patterns of species-specific reactivities [1][2][3][4][5][6][7][8][9]. These observations led to the hypothesis that RF antibodies might arise as part of an idiotype network in which the anti-idiotype to an antibody which specifically recognized a bacterial IgG-Fc-binding protein would result in an internal image of the antigen with similar Fc-binding characteristics [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-IgM Fcp was raised similarly by immunizing the rabbits with Fcp emulsified in Freund's adju vant. Rabbit F(ab'), fragments were prepared as described previ ously [7].…”
Section: Rabbit F(ab')2 Anti-igm Fcand Ffab'f O F Normal Rabbit Iggmentioning
confidence: 99%
“…Although this binding was exerted by IgG Fc receptor-positive streptococci, it was indicated that it took place at sites other than the IgG Fc receptors. The interaction between a mo noclonal RF and type M15 group-A streptococci was further studied and could be ascribed to the anti body-combining site of the RF [7], Thus, streptococci and RF interact with the same site on the IgG Fc molecule, although some RFs can also bind direct to the streptococci via their antibody combining site, which also is responsible for the IgG Fc binding of the RF. The present paper concerns a further investigation of type M15 group A strepto cocci to elucidate this complex pattern.…”
mentioning
confidence: 99%